2009
DOI: 10.1159/000226968
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Gastric Varices Should Not Preclude Prophylactic Ligation of Large Esophageal Varices in Cirrhosis

Abstract: Background/Aims: Coexisting gastric varices at baseline or the risk of their formation during treatment could alter the approach for primary bleeding prophylaxis in patients with large esophageal varices. Methods: Data analysis of 152 patients with cirrhosis and large esophageal varices included in the German multicenter trial on primary prevention of variceal bleeding. Results: 20 patients (13.6%) had coexisting gastric varices at baseline (GOV+). 10 of those each received either band ligation or propranolol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, because the mechanism of varix obliteration differs between EIS and EBL, it is not clear whether EBL also affects portal pressure and GVs development. Some studies have suggested that EVs eradication by EBL is associated with increased portal pressure and risk of bleeding [25], while other studies have suggested that EBL does not affect portal pressure [26] and that it is not associated with GVs development [20]. In the present study, consistent with that latter finding, GVs did not aggravate after EVs eradication by EBL in all enrolled patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, because the mechanism of varix obliteration differs between EIS and EBL, it is not clear whether EBL also affects portal pressure and GVs development. Some studies have suggested that EVs eradication by EBL is associated with increased portal pressure and risk of bleeding [25], while other studies have suggested that EBL does not affect portal pressure [26] and that it is not associated with GVs development [20]. In the present study, consistent with that latter finding, GVs did not aggravate after EVs eradication by EBL in all enrolled patients.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, several previous studies have shown conflicting results regarding the influence of EBL on cardiac varices; in one study, cardiac varices disappeared at similar frequencies between EIS (61.5%) and EBL (50%) [9], while another study suggested that cardiac varices do not disappear after EVs eradication by EBL in patients with GOVs [20]. In the present study, cardiac varices had disappeared in 64.7% of patients with GOV1s who had undergone EVs eradication by EBL.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that EVL results in an increase in the incidence and worsening of portal hypertensive gastropathy [4447]. Others studies have shown that EVL influences also the development of gastric varices [4850].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of recurrent bleeding is dependent on the localization of the varix: isolated varices in the gastric fundus (53%) bear the highest risk of recurrent bleeding, followed by varices of the greater curvature (19%) and lesser curvature (6%) [ 189 ]. The prophylactic treatment of esophageal varices by VBL does not increase the risk of secondary gastric varices compared to propranolol [ 192 ].…”
Section: Gastric Varicesmentioning
confidence: 99%